Association of elevated homocysteine levels and Methylenetetrahydrofolate reductase (MTHFR) 1298 A > C polymorphism with Vitiligo susceptibility in Gujarat. Issue 2 (May 2018) - Jadeja, Shahnawaz D.; Mansuri, Mohmmad Shoab; Singh, Mala; Patel, Hima; Marfatia, Yogesh S.; Begum, Rasheedunnisa
Highlights: Elevated plasma homocysteine and reduced vitamin B12 levels have been demonstrated in vitiligo patients. MTHFR 1298A > C polymorphism was found to be associated with vitiligo. MTHFR 1298A > C polymorphism was correlated with elevated homocysteine levels in vitiligo. In-silico analysis implicated structural changes in MTHFR due to Ala222Val and Glu429Ala substitution. Abstract: Background: Several studies have reported hyperhomocysteinemia in vitiligo patients, suggesting the potential role of elevated homocysteine levels in precipitating vitiligo. Objectives: We aimed to estimate homocysteine and vitamin B12 levels, and to investigate the role of MTHFR 677 C > T and 1298 A > C polymorphisms in vitiligo susceptibility in Gujarat population. Methods: Homocysteine and vitamin B12 levels were estimated in plasma of 55 vitiligo patients and 60 controls by Electrochemiluminescence immunoassay (ECLIA). Polymerase chain reaction- restriction fragment length polymorphism (PCR-RFLP) and amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) techniques were used to genotype MTHFR 677 C > T and 1298 A > C polymorphisms in 520 vitiligo patients and 558 controls. Results: Our results showed significantly elevated homocysteine levels ( p  = 0.0003) as well as significant decrease in vitamin B12 levels ( p  = 0.0102) in vitiligo patients, as compared to controls. No significant difference in genotype and allele frequencies of MTHFR 677 C > T polymorphism was observed among patients and controls, however, the frequency of 'CC' genotype of MTHFR 1298 A > Cpolymorphism was significantly increased in patients as compared to controls ( p  = 0.0151). Analysis based on the type of vitiligo revealed a significant increase in 'C' allele of MTHFR 1298 A > C polymorphism in patients with generalized ( p  = 0.003) and active ( p  = 0.007) vitiligo as compared to controls. Both the polymorphisms of MTHFR were in low linkage disequilibrium (LD) and susceptible 'TC' haplotype was more frequently observed ( p  = 0.008) in vitiligo patients. Interestingly, elevated homocysteine levels were also positively correlated with MTHFR 1298 A > C polymorphism in vitiligo patients. Structure based in silico prediction revealed structural perturbations in MTHFR protein due to Ala222Val and Glu429Ala amino acid substitution. Conclusions: The present findings suggest that MTHFR 1298 A > C polymorphism and, altered homocysteine and vitamin B12 levels might play a vital role in the precipitation of vitiligo.